History of the Baths of Ariño through its analysis - Armijo, Francisco (Anales de Hidrología Médica, 2012)
The possibility of Ariño spring relaunching and transforming it into a spa has motivated us to do a historical study on the characteristics of the water reviewing analytical tests done throughout the years and looking up for related notes written by travelers and guests to the province of Teruel. The study of the constant water composition based on 30 years of analytical results done by several different institutions has been our final objective.